Google Trends as a Tool for Evaluating Public Interest in Facial Cosmetic Procedures. (10th October 2018) - Tijerina, Jonathan D; Morrison, Shane D; Nolan, Ian T; Vail, Daniel G; Nazerali, Rahim; Lee, Gordon K
Abstract: Background: The utility of Google Trends (GT) in analyzing worldwide and regional patient interest for plastic surgery procedures is becoming invaluable to plastic surgery practices. GT data may offer practical information to plastic surgeons pertaining to seasonal and geographic trends in interest in facial cosmetic procedures. Objectives: The authors sought to analyze geographic and temporal trends between GT search volumes and US surgery volumes using univariate analysis. Methods: The "related queries" feature of GT generated potential search terms. GT data were compiled for cheek implants, mentoplasty, otoplasty, blepharoplasty, rhytidectomy, forehead lift, hair transplantation, lip augmentation, lip reduction, platysmaplasty, and rhinoplasty from January 2004 to December 2017. Annual volumes for respective procedures were obtained from annual statistics reports of the American Society of Plastic Surgeons (ASPS) from 2006 to 2017 and American Society of Aesthetic Plastic Surgery (ASAPS) from 2004 to 2017. Results: Geographical and temporal variations in search volume were detected during the study. Search volume trends that correlated significantly with both ASPS and ASAPS surgery volume trends were: "eyelid plastic surgery" (ASPS R 2 = 0.336, P = 0.048; ASAPS R 2 = 0.661, P = 0.001); "facelift" (ASPS R 2 = 0.767, P ≤ 0.001; ASAPS R 2 = 0.767, P = 0.001); "lip injections" (ASPS R 2 = 0.539, P = 0.007; ASAPS R 2 = 0.461, P = 0.044); and "rhinoplasty surgery" (ASPS R 2 = 0.797, P ≤ 0.001; ASAPS R 2 = 0.441, P = 0.01). Several search terms demonstrated no significant relationships or were significant with only one database. Conclusions: GT may provide a high utility for informing plastic surgeons about the interest expressed by our patient population regarding certain cosmetic search terms and procedures. GT may represent a convenient tool for optimizing marketing and advertising decisions.